Clinical Characteristics and Long-Term Outcomes of MINOCA Accompanied by Active Cancer: A Retrospective Insight Into a Cardio-Oncology Center Registry - Stepien, Konrad; Nowak, Karol; Szlosarczyk, Barbara; Nessler, Jadwiga; Zalewski, Jaroslaw (Frontiers in Cardiovascular Medicine, 2022)
Background Clinical characteristics and long-term outcomes of patients with myocardial infarction with non-obstructive coronary arteries (MINOCA) and cancer are insufficiently elucidated. Objectives We sought to characterize these patients hospitalized in a tertiary cardio-oncology center and to find the potential determinants affecting their long-term mortality. Methods MINOCA was diagnosed in 72 of the 1,011 patients with consecutive myocardial infarction who underwent coronary angiography. Mortality rates and their determinants were analyzed within a median follow-up of 69.2 (37.8–79.9) months. Results Active cancer was identified in 21 (29.2%) of patients with MINOCA and in 113 (12.0%) patients with myocardial infarction and obstructive coronary artery disease (MI-CAD) (p < 0.001). MINOCA patients with cancer were characterized by a higher incidence of anemia (47.6 vs. 21.6%, p = 0.03) and more frequently Takotsubo syndrome (19.1 vs. 2.0%, p = 0.01) than in non-cancer MINOCA. The troponin T/hemoglobin ratio was higher in both cancer MINOCA and MI-CAD groups when compared with their respective non-cancer patients (both p < 0.05). The age and sex-standardized mortality rates were significantly higher in cancer MINOCA (26.7%/year) when compared with non-cancer MINOCA (2.3%/year, p = 0.002) and in cancer MI-CAD (25.0%/year) vs. non-cancer MI-CAD (3.7%/year, p < 0.001). Active cancer (HR 3.12, 95% CI 2.41–4.04) was independently associated with higher long-term mortality, while higher hemoglobin levels (HR 0.93, 95% CI 0.88–0.99, per g/dl) and a MINOCA diagnosis (HR 0.69, 95% CI 0.47–0.97) improved long-term survival. Conclusion Patients with MINOCA were comorbid with cancer more frequently than MI-CAD. In turn, an active malignancy was associated with an unfavorable long-term survival both in MI-CAD population and in patients with MINOCA.